Age, growth and life-history parameters of an endemic vulnerable lizard from Patagonia, Argentina - Cabezas, Facundo (2015)
For ectotherms, like lizards, the temperature plays a key role in shaping life history traits such as age and size at sexual maturity, longevity and growth rates. In cold temperate habitats, like Patagonia, lizards must present a very precise balance of the energy expended to growth and reproduction in order to persist in these harsh environments. In the present study, the age and growth of the lizard Phymaturus spectabilis were studied using skeletochronology. We estimated individual ages, growth rates and life history parameters related to growth and reproduction. In our sample juveniles ranged from one to five years old. The youngest adult male was six years and the youngest adult female was seven, though, females seem to live longer as the oldest specimen was a female of 12 years. As a result of short active seasons and thermal constrains characteristics of Patagonia, P. spectabilis presented delayed sexual maturity and medium longevity. Considering the short relative reproductive lifetime, the low frequency of reproduction and the small clutch size P. spectabilis present the lowest net reproductive rate of the liolaemids so far. This suggests that the capability of the population to recover after a disturbance is low, and hence, populations of this species should be protected.